A health economic analysis of an integrated diabetes care program in China: based on real-world evidence - Liang, Di; Zhu, Wenjun; Huang, Jiayan; Dong, Yin (Frontiers in Public Health, 2023)
An integrated care program was set up in China to improve the collaboration between primary healthcare centers and hospitals on diabetes management. This study aims to evaluate the economic value of this program with real-world data and to examine whether it can be promoted in primary healthcare settings in China. This integrated diabetes care program was implemented in Yuhuan City, China, to coordinate primary 2 care and specialty care, treatment and prevention services, as well as the responsibilities of doctors and nurses. Cost-effectiveness analysis was used to compare the short-term economic value of this program (intervention group) versus usual care diabetes management (control group). The cost data were collected from a societal perspective, while the effectiveness indicators pointed to the improvement of control rates of fasting blood glucose (FBG), systolic blood pressure (SBP), and diastolic blood pressure (DBP) levels after the one-year intervention. In addition, cost-utility analysis was applied to evaluate the long-term value of the two groups. Patients' long-term diabetes management costs and quality-adjusted life years (QALYs) were simulated by the United Kingdom Prospective Diabetes Study Outcomes Model 2. The results showed that for 1% FBG, SPB, and DBP control rate improvement, the costs for the intervention group were 290.53, 124.39, and 249.15 Chinese Yuan (CNY), respectively, while the corresponding costs for the control group were 655.19, 610.43, and 1460.25 CNY. Thus, the intervention group's cost-effectiveness ratios were lower than those of the control group.In addition, compared to the control group, the intervention group's incremental costs per QALY improvement were 102.67 thousand CNY, which means that the intervention was cost-effective according to the World Health Organization's standards. In conclusion, this study suggested that this integrated diabetes care program created short-term and longterm economic values through patient self-management support, primary care strengthening, and care coordination. As this program followed the principles of integrated care reform, it can be promoted in China. Also, its elements can provide valuable experience for other researchers to build customized integrated care models.